Genome-wide identification and characterization of putative effectors in Heterodera schachtii that suppress plant immune response - Ke Yao; Menghan Zhang; Jianjun Xu; Deliang Peng; Wenkun Huang; Ling’an Kong; Shiming Liu; Guangkuo Li; Huan Peng (Journal of Integrative Agriculture, 2025)
The sugar beet cyst nematode (Heterodera schachtii) is one of the most destructive pathogens in sugar beet production, which causes serious economic losses every year. Few molecular details of effectors of H. schachtii parasitism are known. We analyzed the genome and transcriptome data of H. schachtii and identified multiple potential predicted proteins. After filtering out predicted proteins with high homology to other plant-parasitic nematodes, we performed functional validation of the remaining effector proteins. 37 putative effectors of H. schachtii were screened based on the Nicotiana benthamiana system for identifying the effectors that inhibit plant immune response, eventually determines 13 candidate effectors could inhibit cell death caused by Bax. Among the 13 effectors, nine have the ability to inhibit GPA2/RBP1-induced cell death. All 13 effector-triggered immunity (ETI) suppressor genes were analyzed by qRT-PCR and confirmed to result in a significant downregulation of one or more defense genes during infection compared to empty vector. For in situ hybridization, 13 effectors were specifically expressed and located in esophageal gland cells. These data and functional analysis set the stage for further studies on the interaction of H. schachtii with host and H. schachtii parasitic control.